2018
DOI: 10.1016/j.bja.2017.11.096
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 is both necessary and sufficient to produce perioperative neurocognitive disorder in mice

Abstract: IL-6 is both necessary and sufficient to produce cognitive decline. Following further preclinical testing of its perioperative safety, the IL6R blocker tocilizumab is a candidate for prevention and/or treatment of PND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 32 publications
3
97
1
2
Order By: Relevance
“…aiming to reveal the underlying mechanisms of POCD and POD. Among these types of surgical trauma, open tibial fracture with intramedullary fixation (Cibelli et al, 2010;Terrando et al, 2010Terrando et al, , 2011Degos et al, 2013;Hu et al, 2018;Ni et al, 2018) and FIGURE 10 | Hippocampal inflammatory trend after tibial fracture surgery. (A) TNF-α mRNA levels were significantly increased on day 1 and returned to control levels on day 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aiming to reveal the underlying mechanisms of POCD and POD. Among these types of surgical trauma, open tibial fracture with intramedullary fixation (Cibelli et al, 2010;Terrando et al, 2010Terrando et al, , 2011Degos et al, 2013;Hu et al, 2018;Ni et al, 2018) and FIGURE 10 | Hippocampal inflammatory trend after tibial fracture surgery. (A) TNF-α mRNA levels were significantly increased on day 1 and returned to control levels on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with exploratory laparotomy, we found that tibial fracture surgery was more suitable for models of POCD and POD in mice, considering its higher survival rate and more standardized procedure (unpublished data). Besides, considering that motor activity was not significantly changed after tibial fracture surgery in most studies (Cibelli et al, 2010;Terrando et al, 2010Terrando et al, , 2011Degos et al, 2013;Hu et al, 2018;Ni et al, 2018), we decided to apply this trauma model in the present study. Unfortunately, however, we found that motor activity was actually affected after tibial surgery (Figure 2), which might be attributed to the higher age of the mice we used (12-14 months) while the studies mentioned above used adult rodents around 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation and pro-inflammatory cytokines released after surgery have been associated with changes in neuronal function and are highlighted as critical pathogenic mechanisms underlying cognitive decline in preclinical models. 16 , 17 , 18 Because SPMs provide both anti-inflammatory and pro-resolving actions without being immunosuppressive, 19 we tested the hypothesis that targeting macrophage trafficking into the brain using synthetic MaR1 will reduce neuroinflammation and improve cognitive outcome in a murine model of orthopaedic surgery. We also provide preliminary evidence that MaR1 levels can be measured in human cerebrospinal fluid (CSF) before and after surgery, raising the possibility that MaR1 levels could potentially play a role in resolving postoperative neuroinflammation in the human CNS.…”
mentioning
confidence: 99%
“…В експериментальній роботі на мишах доведено негативний вплив ІЛ-6 на післяопераційну нейрокогнітивну функцію [9]. У людей похилого віку високі рівні ІЛ-6 і низькі ІЛ-2 у періопераційному періоді асоціюються з великим ризиком розвитку післяопераційного делірію [10,11].…”
Section: вступunclassified